Effects on larval metamorphosis in the mussel Mytilus coruscus of compounds that act on downstream effectors of G-protein-coupled receptors. (11th October 2016) - Liang, Xiao; Chen, Yu-Ru; Gao, Wei; Guo, Xing-Pan; Ding, De-Wen; Yoshida, Asami; Osatomi, Kiyoshi; Yang, Jin-Long
Abstract : The metamorphic responses of mussel ( Mytilus coruscus ) larvae to pharmacological agents affecting G proteins and the adenylate cyclase/cyclic AMP (AC/cAMP) pathway were examined in the laboratory. The G protein activators guanosine 5′-[β, γ-imido]triphosphate trisodium salt hydrate and guanosine 5′-[γ-thio]triphosphate tetralithium salt only induced larval metamorphosis in continuous exposure assays, and the G protein inhibitor guanosine 5′-[β-thio]diphosphate trilithium salt did not exhibit inducing activity. The non-specific phosphodiesterase inhibitor theophylline and the cAMP-specific phosphodiesterase IV inhibitor 4-(3-Butoxy-4-methoxybenzyl)imidazolidin-2-one exhibited inducing activity, while the non-specific phosphodiesterase inhibitor 3-Isobutyl-1-methylxanthine only showed inducing activity at 10 −4 M in continuous exposure assays. The cyclic nucleotide analogue N 6, 2′-O-Dibutyryladenosine 3′, 5′-cyclic monophosphate sodium salt did not exhibit significant inducing activity. Both the adenylate cyclase activator forskolin and the adenylate cyclase inhibitor nitroimidazole exhibited inducing activity at 10 −4 to 10 −3 M concentrations in continuous exposure assays. Among these tested agents, the adenylate cyclase inhibitor (±)-miconazole nitrate salt showed the most promising inducing effect. The present results indicate that G protein-coupled receptors and signal transduction by AC/cAMP pathway could mediate metamorphosis of larvae in this species.